Biceps Femoris Fascicle Lengths Increase after Hamstring Injury Rehabilitation to a Greater Extent in the Injured Leg. (22nd September 2022) - Whiteley, Rod; Hickey, Jack T.; Vermeulen, Robin; Timmins, Ryan; Best, Thomas M.; Rio, Ebonie; Opar, David
Abstract : Objectives . Document changes in fascicle length during rehabilitation from hamstring injury of the injured and uninjured legs and secondarily to describe any association between these changes and reinjury rate. Design . Multicentre case series. Methods . Fifty-two prospectively included hamstring injured athletes had their biceps femoris long head fascicle lengths measured at the start and end of rehabilitation using two-dimensional ultrasound. Absolute and relative changes in fascicle length were compared for each leg using linear mixed models. Participants were followed for six months after being cleared to return to sport for any reinjury. Fascicle lengths and rehabilitation duration were compared for those who reinjured and those who did not. Results . Injured leg fascicle length was shorter at the start of rehabilitation (9.1 cm compared to 9.8 cm, p < 0.01 ) but underwent greater absolute and relative lengthening during rehabilitation to 11.1 cm (18% increase) compared to 10.2 cm (8% increase, p < 0.01 ) for the uninjured leg. There were no significant differences in any fascicle length parameter for the 5 participants who reinjured in the 6 months following their return to sport compared to those that did not reinjure. Conclusions . While both injured and uninjured legs displayed increases in fascicle length during rehabilitation, the larger fascicle length increases in the injured leg suggest that either a different training stimulus was applied during rehabilitation to each leg or there was a different response to training and/or recovery from injury in the injured leg. Reinjury risk appears to be independent of fascicle length changes in this cohort, but the small number of reinjuries makes any conclusions speculative.